Pain Perception after Periodontal Therapies - Pradhan, Shaili; Shrestha, Regina; Gorkhali, Ranjita Shrestha (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Background: Pain perception is a complex sensory experience which is perceived by different individuals in different manners. The pain perceived by the patient after periodontal surgery may vary based on different parameters. Aim: This observational study was conducted to evaluate the perception of pain after periodontal therapies. Materials and Methods: A total of 63 surgeries were carried out in 50 patients and the surgeries were divided into three categories: open flap debridement, resective and regenerative surgeries, and periodontal plastic surgeries. The pain experienced by the patient was recorded on the visual analog scale that ranged from 0 to 10. Results: The mean VAS score for different periodontal surgeries was 2.49. The study showed highest mean VAS in open flap debridement (2.74) followed by periodontal plastic surgery (2.5) and the lowest in resective and regenerative procedures (2.13). Among various variables such as age, sex, periodontal dressing, arch, amount of local anaesthesia and time duration, the data showed statistical difference between VAS score and sex (p = 0.04) and between VAS score and amount of local anaesthesia (p = 0.012). Conclusion: The study showed there is low pain perception after different periodontal surgeries as measured by VAS. Proper understanding of the variables that affect pain is important as they may produce emotional responses that could influence compliance and the therapy result. Inadvertent use of large dose of anaesthetics beforehand assuming high anticipation of pain should be discouraged as the increase in volume relates to increased pain.